Socio-Psychological Impact of Outdoor Sculptures in Nigeria Urban Cities - Allan Francis Ebunola Oladugbagbe (Journal of Visual Art and Design, 2016)
One major element that finds expression at road intersections, parks, gardens, square and open spaces in the urban landscape are outdoor sculptures. Of great significance is the historical information they disseminate, the visual impressions they convey and the aesthetic value they add to the quality of the city. From 1960s and after the civil war, the uses of sculptures for embellishments in public places have increased tremendously in Nigeria. However, outdoor sculpture for the purpose of recreation and relaxation in our built environment has not been adequately addressed scholastically in Nigeria. This paper, therefore, focuses on the social values derivable from the use of sculpture in urban design and the losses that could accrue to the social system if not adequately managed. The values of these sculptures to the socio-psychological development of Nigerians and the beautification of the urban environment are equally emphasized. The study shows that incorporating sculptures into public places without doubt will heighten public appreciation and aesthetic perception and make Nigerian cities unique and vibrant.Keywords: Nigeria urban cities; socio-psychological impact; outdoor sculptures.